Influence of neutral protease activity on human islet isolation outcome. - Brandhorst, H; Brendel, MD; Eckhard, M; Bretzel, R; Brandhorst, D (2005)
Observations in rat pancreata have revealed that enzymatic islet release is mediated by both collagenase and neutral protease (NP), a critical effector of islet integrity. Since no information is available about the effect of NP activity on islet release from the human pancreas, the present study evaluated the effect of various NP concentrations on the outcome of human islet isolation. METHODS: Following intraductal collagenase distension, pancreata obtained from adult multiorgan donors were digested using 2000 PZ-U of purified Serva collagenase NB 1 supplemented with 2.6 (n = 10) or 4.5% (DMC-U/PZ-U) (n = 10) of NP. RESULTS: Increasing NP from 2.6% to 4.5% reduced the amount of undigested tissue from 22 +/- 2 to 17 +/- 2 g (P < .05) while simultaneously increasing the volume of digested tissue (26 +/- 2 vs 40 +/- 3 mL, P < .01). Increased NP concentrations increased the islet yield prepurification (459,800 +/- 22,900 vs 587,600 +/- 69,000 IEQ, P < .05), but simultaneously affected islet purification, resulting in equal islet yields (345,700 +/- 31,200 vs 391,500 +/- 35,400 IEQ, NS) and less purity (70 +/- 6 vs 49% +/- 5%, P < .01). A NP concentration of 4.5% reduced the stimulation index (4.7 +/- 1.2 vs 2.0 +/- 0.5, P < .01) and viability (100 +/- 1 vs 95% +/- 3%, P < .05). CONCLUSIONS: Although increased NP activity seems to improve islet release from adult human pancreata, it significantly affects islet viability and function. The reduction in purity reflected damage to acinar tissue by increased NP activity presumably affecting islet integrity.